The Effect of Profitability, Liquidity, Asset Structure, Sales Growth and Business Risk on Capital Structure (Empirical Study of Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange 2018-2021) - Cathrine Dewi Tanuraharja; Peng Wi (Global Accounting, 2023)
The purpose of this study is to demonstrate the impact of profitability, liquidity, asset structure, earnings growth and business risk on capital structure. The dependent variable in this study is capital structure, and the independent variables are profitability, liquidity, asset structure, earnings growth, and earnings growth of IDX-listed food and beverage subsector manufacturing companies from 2018 to 2021. It's a business risk. The ponder populace was 45 companies. The sort of information utilized in this consider is auxiliary information employing a deliberate inspecting method for test determination. The tests utilized in this ponder included 80 tests. The information examination strategies utilized in this think about are expressive measurements, classical presumptions, and theory testing utilizing SPSS adaptation 25 program.                 Profitability, sales growth, and business risk have no affect on capital structure based on subtest comes about. On the other hand, liquidity and asset structure have a clear positive affect on capital structure. The concurrent test comes about appear that profitability, liquidity, asset structure, earnings growth, and business risk all at the same time have a positive affect on capital structure.